AVALIAÇÃO DOS EFEITOS CITOTÓXICOS DE COMPOSTOS CONTENDO O RADICAL FARMACOFÓRICO 1,4-DIOXO-2-BUTENIL EM SISTEMA IN VITRO - Simone Zacalusni (2023)
Cancer reached more than 19.3 million new cases worldwide in 2020, leading to the death of almost 10.0 million people. Adding this to the high costs of treating the disease, the importance of studying new molecular structures and the design/construction of new substances that could be used in the treatment of this disease or in adjuvant therapy is emphasized. Study of compounds containing 1,4-dioxo-2-butenyl were evaluated in human and murine cells and demonstrated cytotoxic potential. In this study, the cytotoxic effects of two compounds containing the pharmacophore radical 1,4-dioxo-2-butenyl in an in vitro system were evaluated. The HT-29 human colorectal adenocarcinoma cell line treated with different concentrations of Aryl-Maleamic Acid (A6) or p-chloro phenyl-maleimide (M2) were used. Cytotoxicity assessment was performed by the colorimetric MTT test. The results demonstrated A6 is cytotoxic from concentrations of 125, 250 and 125 µg/mL for the times of 24, 48 and 72h, respectively. On the other hand, M2 was cytotoxic from the concentration of 1.9 µg/mL for the three times tested. The IC50 of A6 and M2 were 378.8 ± 22.0µg/ml, respectively. These results suggest that M2 has therapeutic potential for the treatment of cancer.